First Finding of Acanthocephalans Arhythmorhynchus invaginabilis, Southwellina hispida (Acanthocephales, Polymorphidae), Plagiorhynchus (Plagiorhynchus) odhneri (Acanthocephales, Plagiorhynchidae) in the Intermediate Hosts - Lisitsyna, O.I. (Вестник зоологии, 2011)
The acanthocaphalan larvae of Arhythmorhynchus invaginabilis, Southwellina hispida, Plagiorhynchus (Plagiorhynchus) odhneri, parasites of waterfowl, were found for the first time in intermediate hosts, amphipods of the family Tallitridae. Larvae are described, drawn and and photomicrographed. Личинки акантоцефалов трех видов, Arhythmorhynchus invaginabilis, Southwellina hispida, Plagiorhynchus (Plagiorhynchus) odhneri, паразитов водно-болотных птиц, впервые обнаружены у амфипод сем. Tallitridae, промежуточных хозяев. Приведены описания, рисунки и фотографии найденных личинок.